2012
DOI: 10.3390/ijgi1010003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Urban Land Cover Growth Dynamics Using Multi‑Temporal Satellite Images: A Case Study of Dhaka, Bangladesh

Abstract: Abstract:The primary objective of this research is to predict and analyze the future urban growth of Dhaka City using the Landsat satellite images of 1989, 1999 and its surrounding impact areas have been selected as the study area. At the beginning, a fisher supervised classification method has been applied to prepare the base maps with five land cover classes. In the next stage, three different models have been implemented to simulate the land cover map of Dhaka city of 2009. These have been named as "Stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(149 citation statements)
references
References 22 publications
4
143
1
1
Order By: Relevance
“…The MLP is one of the most suitable algorithms for classification and prediction of LULC changes and able to solve non-linear separable problems (Ahmed & Ahmed, 2012). Based on the supervized Backpropagation (BP) algorithm, the MLP is a feed forward artificial neural network model that maps sets of input data into a set of appropriate output.…”
Section: Transition Potential Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLP is one of the most suitable algorithms for classification and prediction of LULC changes and able to solve non-linear separable problems (Ahmed & Ahmed, 2012). Based on the supervized Backpropagation (BP) algorithm, the MLP is a feed forward artificial neural network model that maps sets of input data into a set of appropriate output.…”
Section: Transition Potential Modelingmentioning
confidence: 99%
“…Several studies have revealed that the integrated MultiLayer Perceptron-Markov chain analysis (MLP-MCA) method is a robust tool to quantify and model the spatio-temporal LULC changes that combines remote sensing and GIS efficiently (Ahmed & Ahmed, 2012;Mishra et al, 2014;Ozturk, 2015). In the MLP-MCA hybrid model, the MLP neural network is trained by supervized backpropagation (BP) algorithm with efficient generalization capability for each LULC transition and simulation (Maithani, 2015), while the MCA model determines transition probability areas to predict likely LULC changes in the future (Dadhich & Hanaoka, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The overall accuracy was calculated separately for each time point (1995, 2005 and 2015) [38]. The result accuracies of the accuracy assessment of the LULC classification were 77.4%, 79.6% and 76.8% for 1995, 2005, and 2015, respectively [39]. (See Appendix A for more details).…”
Section: Assessing the Accuracy Of Lulc Mapsmentioning
confidence: 99%
“…However, other non-structural measures such as land use planning can play important role for reducing flood risk. Dewan and Yamaguchi (2009) and Ahmed and Ahmed (2012) …”
Section: Resultsmentioning
confidence: 99%